2018
DOI: 10.1109/tbme.2017.2717280
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Lung Sound Screening for Pediatric Auscultation in Noisy Field Environments

Abstract: Unlike existing methodologies in the literature, the proposed work is not limited in scope or confined to laboratory settings: This work validates a practical method for fully automated chest sound processing applicable to realistic and noisy auscultation settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…Other sound assessment Several recent audio processing methods have been proposed regarding non-cry signals and concerning either pre-linguistic vocalizations (including cooing) (Fuller andHorii, 1986, 1988;Pokorny et al, 2016Pokorny et al, , 2018. Non-voice analyses were also proposed in different contexts such as external noise detection (Raboshchuk et al, 2018a,b), EEG sonification (Gomez et al, 2018) or lung sound assessment (Emmanouilidou et al, 2017).…”
Section: Automatic Cry Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other sound assessment Several recent audio processing methods have been proposed regarding non-cry signals and concerning either pre-linguistic vocalizations (including cooing) (Fuller andHorii, 1986, 1988;Pokorny et al, 2016Pokorny et al, , 2018. Non-voice analyses were also proposed in different contexts such as external noise detection (Raboshchuk et al, 2018a,b), EEG sonification (Gomez et al, 2018) or lung sound assessment (Emmanouilidou et al, 2017).…”
Section: Automatic Cry Segmentationmentioning
confidence: 99%
“…It was shown that sonification methods perform similarly well, with a smaller inter-observer variability in comparison with visual interpretation. Lung audio recordings of 1000 children were also studied (Emmanouilidou et al, 2017). First, noise suppression techniques were applied to discard ambient sounds, sensors artifacts or crying.…”
Section: Automatic Cry Segmentationmentioning
confidence: 99%
“…14 We have also developed and internally validated a fully automated lung sound processing algorithm that can identify abnormal lung sounds from PERCH recordings with nearly 90% accuracy. 13 In this research, we extend this initial body of work to show that human interpretation of digital lung recordings has important clinical relationships with radiographic pneumonia and pneumonia mortality. While these results are encouraging it is important to stress that they should be considered as only an initial step towards clinical or research application given the lack of a gold standard for pneumonia diagnosis and the inherent limitations of the WHO-defined radiographic pneumonia methodology, as discussed below.…”
Section: Digitally Recorded Lung Sounds and Mortalitymentioning
confidence: 80%
“…On ICBHI17 dataset, an accuracy of 52.26% was reported. Emmanouilidou et al [ 11 ] proposed a robust approach to identify lung sounds in the presence of noise. In their experiments, with 1K+ volunteers (over 250 hours of data), an accuracy of 86.7% was reported.…”
Section: Introductionmentioning
confidence: 99%